2023
DOI: 10.1038/s42003-023-04479-w
|View full text |Cite
|
Sign up to set email alerts
|

Murine breast cancers disorganize the liver transcriptome in a zonated manner

Abstract: The spatially organized gene expression program within the liver specifies hepatocyte functions according to their relative distances to the bloodstream (i.e., zonation), contributing to liver homeostasis. Despite the knowledge that solid cancers remotely disrupt liver homeostasis, it remains unexplored whether solid cancers affect liver zonation. Here, using spatial transcriptomics, we thoroughly investigate the abundance and zonation of hepatic genes in cancer-bearing mice. We find that breast cancers affect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Comprehensive measurements of diverse genes and molecules (i.e., omics analysis) against host organs and cells in cancer-bearing conditions is a promising method to understand cancer's adverse effects on the host. To date, a relatively non-biased approach led to the identification of altered metabolism in various metabolic organs, dysregulation in the immune system, and so on., as exemplified by but not limited to a series of previous reports 13,14,15,16,17,18,19 . Measuring molecules from different sources (e.g., blood and immune cells) is of particular significance because it would enable the thorough characterization of disrupted homeostasis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Comprehensive measurements of diverse genes and molecules (i.e., omics analysis) against host organs and cells in cancer-bearing conditions is a promising method to understand cancer's adverse effects on the host. To date, a relatively non-biased approach led to the identification of altered metabolism in various metabolic organs, dysregulation in the immune system, and so on., as exemplified by but not limited to a series of previous reports 13,14,15,16,17,18,19 . Measuring molecules from different sources (e.g., blood and immune cells) is of particular significance because it would enable the thorough characterization of disrupted homeostasis.…”
Section: Introductionmentioning
confidence: 85%
“…We do not exclude the possibility of the involvement of other non-immune cell types, such as hepatocytes and muscle cells, in the immunosuppressive phenotypes. Hepatocytes are the major site of albumin production 14 . Thus, low albumin status most likely indicates liver abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…28 We observed that, in control mice, expression of genes associated with the "xenobiotic catabolic process" was highly active in hepatocytes harboring high expression of Cyp2e1, a marker for liver zonation. 28 However, this localized expression was not observed in the livers of 4T1-bearing mice, suggesting that the presence of 4T1 breast cancer disrupted zonated expression of genes involved in the "xenobiotic catabolic process. 28 " In addition, we discovered cancer-induced switching of the biological functions of Albumin (Alb)-high hepatocytes in the liver from metabolism to acute phase response.…”
Section: Disruption In Liver Zonationmentioning
confidence: 87%
“…28 However, this localized expression was not observed in the livers of 4T1-bearing mice, suggesting that the presence of 4T1 breast cancer disrupted zonated expression of genes involved in the "xenobiotic catabolic process. 28 " In addition, we discovered cancer-induced switching of the biological functions of Albumin (Alb)-high hepatocytes in the liver from metabolism to acute phase response. 28 In 4T1-bearing mice, genes associated with the "acute phase response" were upregulated in a zonated manner, having higher expression levels in Alb-high zones.…”
Section: Disruption In Liver Zonationmentioning
confidence: 98%
See 1 more Smart Citation